PENGEMBANGAN GAME EDUKATIF DAN BAHAN AJAR MATEMATIKA SEKOLAH MENENGAH PERTAMA KELAS VII BERBASIS ANDROID - Mubarak, Sultan Fadel; Irwan, Irwan; Agita Rindri, Yang (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
In the era of globalization, technological developments have increased rapidly, this has a positive impact in various fields, especially education. The utilization of technology, information, and communication is used to improve efficiency and effectiveness in the teaching and learning process. Less varied mathematics learning will complicate the development of students' skill of thingking. In the learning process, interactive learning media are needed for students which can easily get bored while receiving learning material from teacher. Applications are made using the Research and Development (R&D) method, namely research conducted to test the effectiveness and efficiency of certain products (Sugiyono 2010). As for the development model, implementing the ADDIE development model is a development model consisting of 5 phase, which containing by Analysis, Design, Development, Implementation, and Evaluating of application. The outcome of the research will be implemented into an Android-Based Educational Game Application and Mathematics Teaching Materials for Junior Middle School. The material presented in the application is validated first by material experts and media experts. The application that is run is by the current curriculum and the application can run according to the prototype design.